The importance of police public relations in assembly situations - Grutzpalk, Jonas (Public Order Policing, 2024)
Police operations do not occur in a vacuum, but rather are accompanied by a media public. This public is difficult to understand, consisting of confusing echo chambers, fake news, journalism, social media, and rapid attention economies. Police are obliged to simultaneously explain their own actions and to reinforce the public’s sense of security through the media. This mix becomes a challenge for the police, especially in assembly situations, when there are real-time media disputes about how a situation unfolds and is interpreted. Recommendations are provided to advise police public relations, from a German perspective, on how to position themselves within this media situation.